An Analysis of Anatomic Variations of the Sphenoid Sinus and Its Relationship to the Internal Carotid Artery - Dal Secchi, Myrian Marajó; Dolci, Ricardo Landini Lutaif; Teixeira, Reginaldo; Lazarini, Paulo Roberto (International Archives of Otorhinolaryngology, 2018)
Introduction The sphenoid sinus (SS) has a high variability; its anatomical relations and variations must be well understood prior to the expanded endoscopic surgery (EES) at the skull base via the endonasal transsphenoidal approach. A feared complication is injury to the internal carotid artery (ICA).Objective To evaluate the anatomic variations of the SS and its relationship to the ICA using computed tomography (CT).Methods Cross-sectional retrospective study. Analysis of 90 patients' CT scans on axial, coronal and sagittal planes with 1 mm slices, evaluating lateral and posterior extensions of pneumatization of the SS, deviation of the sphenoid septum, presence of septations and their relationship to the parasellar and paraclival segments of the internal carotid artery (psICA and pcICA, respectively).Results The association between the protrusions of the psICA and the pcICA was statistically significant (p < 0.001), as was the association between the lateral extension of pneumatization of the SS and the protrusion of the psICA (p = 0.014). The presence of the posterior extension of pneumatization of the SS and protrusion of the pcICA occurred in 46% of the cases. Deviation of the sphenoid septum in the direction of the pcICA was present in 14% and dehiscence of the pcICA was seen in 3.6% of the cases.Conclusion Using the CT scan to recognize the type of extensions of pneumatization of the SS, the deviation of the sphenoid septum, and the presence of septations is beneficial to identify accurately the ICA and to reduce the risk of injury to it.
Keywords: carotid artery; internal; paranasal sinuses/surgery; skull base; sphenoid sinus; sphenoid bone; tomography; X-ray computed